Phonological Aspects in the Arabic Dictionary: The Arabic Dictionary in your Hands as an Example Namûzajan/ Al-Jawậnibu as-Shautiyah fi al-Mu’jam al-Arabiy: Al-Mu’jam al-Arabiyu baina Yadaik - Muzadi, Narul Hasyim (Al-Manar, 2024)
AbstractAs a system, language is both a systematic and a subsystem. One of the subsystems is phonology. Phonology is a field or level of study in linguistics that discusses everything related to the sounds of language. Phonetics as a branch of phonetics discusses the sounds of language that do not affect meaning, while phonology discusses the sounds of language that affect meaning. This research belongs to the category of qualitative research with a literary study approach. The data collection method used in this research is to collect textbooks, journals, scientific articles, and literature reviews that contain the concept under study. The primary data source for this research is the dictionary of Abdul Rahman bin Ibrahim Al-Fouzan, Mukhtar Al-Tahir Hussein, and Muhammad Abdul Khaliq Muhammad Fadl titled "The Arabic Dictionary Baina Yadaik". The data analysis method used in this research is content analysis. The flow used to analyze the data is: Data reduction, data presentation, and drawing conclusions. The goals of studying the phonetics aspects of the Arabic Lexicon "In Your Hands" are invaluable, as phonetics is an important foundation for understanding and using the Arabic language correctly. By understanding phonics, learners can master correct pronunciation, distinguish between similar meanings, enhance listening skills, expand their vocabulary, and understand the structure of the language more deeply.Key words: Phonetics, Arabic Lexicon, Baina Yadaikملخص البحثوباعتبارها نظاما، فإن اللغة نظام منهجي وفرعي. أحد الأنظمة الفرعية هو علم الأصوات. وعلم الأصوات هو أحد مجالات أو مستويات الدراسة في علم اللغة الذي يناقش كل ما يتعلق بأصوات اللغة. ويناقش علم الصوتيات كفرع من فروع علم الأصوات الأصوات أصوات اللغة التي لا تؤثر على المعنى، بينما يناقش علم الأصوات أصوات اللغة التي تؤثر على المعنى. ينتمي هذا البحث إلى صنف البحوث الكيفية ذات منهج الدراسة الأدبية. ويتمثل أسلوب جمع البيانات المستخدم في هذا البحث في جمع الكتب المدرسية والمجلات والمقالات العلمية والمراجعات الأدبية التي تحتوي على المفهوم قيد الدراسة. ومصدر البيانات الأساسية في هذا البحث هو معجم عبد الرحمن بن إبراهيم الفوزان، ومختار الطاهر حسين، ومحمد عبد الخالق محمد فضل بعنوان "المعجم العربي بين يديك". أسلوب تحليل البيانات المستخدم في هذا البحث هو تحليل المضمون. إن التدفق المستخدم في تحليل البيانات هو: اختزال البيانات، وعرض البيانات، واستخلاص النتائج. أهداف من دراسة جوانب الصوتيات في المعجم العربي "بين يديك" لا تقدر بثمن، حيث تشكل الصوتيات أساسا هاما لفهم واستخدام اللغة العربية بشكل صحيح. من خلال فهم الصوتيات، يمكن للمتعلمين أن يتقنوا النطق الصحيح، ويميزوا بين المعاني المتشابهة، ويعززوا مهارات الاستماع، ويوسِّعوا مفرداتهم، ويفهموا بنية اللغة بعمق أكبر.الكلمات الرئيسية: الجوانب الصوتية، المعجم العربي، بين يديك